1974
DOI: 10.1152/ajplegacy.1974.226.6.1298
|View full text |Cite
|
Sign up to set email alerts
|

Beta-adrenergic effects on rat myometrium: role of cyclic AMP

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
15
0
2

Year Published

1975
1975
2008
2008

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 0 publications
4
15
0
2
Order By: Relevance
“…Catecholamines may cause relaxations of some smooth muscles (8)(9)(10)(11)(12)(13)(14), some vascular smooth muscles (8,(15)(16)(17), uterus (8,(18)(19)(20)(21)(22)(23). The action of catecholamines son these muscles is mainly due to beta-adrenoceptor activation and able to be blocked by beta-adrenergic blocking agents (12-14, 17, 19).…”
Section: And Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Catecholamines may cause relaxations of some smooth muscles (8)(9)(10)(11)(12)(13)(14), some vascular smooth muscles (8,(15)(16)(17), uterus (8,(18)(19)(20)(21)(22)(23). The action of catecholamines son these muscles is mainly due to beta-adrenoceptor activation and able to be blocked by beta-adrenergic blocking agents (12-14, 17, 19).…”
Section: And Discussionmentioning
confidence: 99%
“…The action of catecholamines son these muscles is mainly due to beta-adrenoceptor activation and able to be blocked by beta-adrenergic blocking agents (12-14, 17, 19). Cyclic adenosine-3', 5'-monosphosphate (cyclic AMP) is believed to be the intracellular mediator of the effect of beta-adrenoceptor activation in the smooth muscles mentioned above (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). On the other hand, alpha-adrenoceptor activation may also cause relaxation of intestinal smooth muscle (9,(12)(13)(14).…”
Section: And Discussionmentioning
confidence: 99%
“…Ortamda agonist madde bulunduğu sürece sitoplazmada siklik AMP birikimi olur, siklik AMP (Adenozin monofosfat) Beta adrenerjik aktivasyonda hücre içi olaylarda ikinci ulak (sekonder messenger) görevi yapar (5,16,21,24,38).…”
Section: Introductionunclassified
“…Beta-adrenerjik res eptörlerin aktivasyonunda hücre içi kalsiyum yoğunluğu azalır (19,24,28 Grafik: 5 ve 6 Mg varlıgı ve yoklugunda Dibutiril siklik AMP'nin potasyum kontraksiyonundakietkilerine ait dozeCevap ilişkisi Grafik: 3.5 ostrojen, 3.6 ise progesteron uygulanmış tavşanlardan alınan test dokularındaki sonuçları göstermektedir. …”
Section: Introductionunclassified
“…Since Bueding, Butcher, Hawkins, Timms & Sutherland (1966) suggested that this effect was related to activation of adenyl cyclase, many investigators have shown that the cyclic AMP level in smooth muscle is directly related to smooth muscle tone, i.e. increase in cyclic AMP causes relaxation of visceral smooth muscle (Andersson, Lundholm, Mohme-Lundholm & Nilsson, 1972;Schultz, Schultz & Hardman, 1975;Bar, 1974;Kroeger & Marshall, 1974;Triner, Nahas, Vullienoz, Overweg, Verosky, Habif & Ngai, 1975;Kroeger, Teo, Ho & Wang, 1975;Honeyman, Merrian & Fay, 1978). This postulation has been confirmed and extended by further investigations.…”
mentioning
confidence: 99%